The Effect of Fractional CO2 Laser Irradiation on Shear Bond Strength of Resin Cement to Feldspathic Porcelain - Ahrari, Farzaneh; Boruziniat, Alireza; Mohammadipour, Hamideh Sadat; Alirezaei, Mehrnoosh (Journal of Lasers in Medical Sciences, 2018)
Introduction: This study investigated the effect of fractional CO2 laser on shear bond strength (SBS) of resin cement to feldspathic porcelain. Methods: Sixty blocks of unglazed feldspathic porcelain were randomly divided into 5 groups of 12 by treatment. Group 1 and 2 underwent etching with 9.6% hydrofluoric acid (HF) and air abrasion with alumina particles, respectively. In groups 3 and 4, a fractional CO2 laser was applied for 10 seconds using 20 W/10 mJ (group 3) or 15 W/20 mJ (group 4). The specimens in group 5 were first treated by fractional CO2 laser (15 W/20 mJ) and then etched by HF acid. After silane application, a resin cement (Clearfil SA) was poured into plastic molds over the porcelain surface and light cured. SBS was assessed by a universal testing machine and the type of bond failure was determined. Results: Analysis of variance (ANOVA) indicated a significant difference in SBS among the study groups (P < 0.001). Pairwise comparison demonstrated that the application of fractional CO2 laser followed by HF acid yielded SBS that was significantly greater than that of the other groups (P < 0.05). The SBS of both laser groups (groups 3 and 4) were comparable to each other and significantly lower than the other groups (P < 0.05). No significant difference was found in the distribution of failure modes among the groups (P = 0.522) Conclusion: The application of fractional CO2 laser followed by HF acid treatment can improve SBS of resin cement to feldspathic porcelain and could be recommended when demanding extra retention.